병원건물에너지 절감을 위한 진단/평가방법 체계화 및 에너지관리 프로세스 개발 - 조진균(Jinkyun Cho); 박병용(Beungyong Park); 서한석(Hansuk Seo) (설비공학 논문집, 30(8), 2018)
Because a hospital building operates 24 hours a day, 365 days a year, for treatment and restoration of patients, it has a different pattern of energy use than that of ordinary buildings. In this study, we proposed an energy diagnosis, evaluation method and energy management process needed to verify energy saving by using operational data based on system and facility characteristics, operation patterns, and energy consumption characteristics of a hospital building. Surveying cases in hospitals, an energy saving of about 10 percent could be expected from energy efficiency, control, and demand management rather than from simple replacement of equipment and systems. Field surveys and preliminary evaluation methods, remote energy-data collection, and study of energy-related factors have become fundamental for implementing a more effective and systematic operational data-based diagnosis/evaluation process for hospital energy savings.